OM/Claudio_Maggioni_midterm/Claudio_Maggioni_midterm.md
Claudio Maggioni (maggicl) 87746f945f midterm: done 1
2021-05-03 11:28:46 +02:00

142 lines
5.0 KiB
Markdown

<!-- vim: set ts=2 sw=2 et tw=80: -->
---
header-includes:
- \usepackage{amsmath}
- \usepackage{hyperref}
- \usepackage[utf8]{inputenc}
- \usepackage[margin=2.5cm]{geometry}
---
\title{Midterm -- Optimization Methods}
\author{Claudio Maggioni}
\maketitle
# Exercise 1
## Point 1
### Question (a)
As already covered in the course, the gradient of a standard quadratic form at a
point $x_0$ is equal to:
$$ \nabla f(x_0) = A x_0 - b $$
Plugging in the definition of $x_0$ and knowing that $\nabla f(x_m) = A x_m - b
= 0$ (according to the first necessary condition for a minimizer), we obtain:
$$ \nabla f(x_0) = A (x_m + v) - b = A x_m + A v - b = b + \lambda v - b =
\lambda v $$
### Question (b)
The steepest descent method takes exactly one iteration to reach the exact
minimizer $x_m$ starting from the point $x_0$. This can be proven by first
noticing that $x_m$ is a point standing in the line that first descent direction
would trace, which is equal to:
$$g(\alpha) = - \alpha \cdot \nabla f(x_0) = - \alpha \lambda v$$
For $\alpha = \frac{1}{\lambda}$, and plugging in the definition of $x_0 = x_m +
v$, we would reach a new iterate $x_1$ equal to:
$$x_1 = x_0 - \alpha \lambda v = x_0 - v = x_m + v - v = x_m $$
The only question that we need to answer now is why the SD algorithm would
indeed choose $\alpha = \frac{1}{\lambda}$. To answer this, we recall that the
SD algorithm chooses $\alpha$ by solving a linear minimization option along the
step direction. Since we know $x_m$ is indeed the minimizer, $f(x_m)$ would be
obviously strictly less that any other $f(x_1 = x_0 - \alpha \lambda v)$ with
$\alpha \neq \frac{1}{\lambda}$.
Therefore, since $x_1 = x_m$, we have proven SD
converges to the minimizer in one iteration.
## Point 2
The right answer is choice (a), since the energy norm of the error indeed always
decreases monotonically.
To prove that this is true, we first consider a way to express any iterate $x_k$
in function of the minimizer $x_s$ and of the missing iterations:
$$x_k = x_s + \sum_{i=k}^{N} \alpha_i A^i p_0$$
This formula makes use of the fact that step directions in CG are all
A-orthogonal with each other, so the k-th search direction $p_k$ is equal to
$A^k p_0$, where $p_0 = -r_0$ and $r_0$ is the first residual.
Given that definition of iterates, we're able to express the error after
iteration $k$ $e_k$ in a similar fashion:
$$e_k = x_k - x_s = \sum_{i=k}^{N} \alpha_i A^i p_0$$
We then recall the definition of energy norm $\|e_k\|_A$:
$$\|e_k\|_A = \sqrt{\langle Ae_k, e_k \rangle}$$
We then want to show that $\|e_k\|_A = \|x_k - x_s\|_A > \|e_{k+1}\|_A$, which
in turn is equivalent to claim that:
$$\langle Ae_k, e_k \rangle > \langle Ae_{k+1}, e_{k+1} \rangle$$
Knowing that the dot product is linear w.r.t. either of its arguments, we pull
out the sum term related to the k-th step (i.e. the first term in the sum that
makes up $e_k$) from both sides of $\langle Ae_k, e_k \rangle$,
obtaining the following:
$$\langle Ae_{k+1}, e_{k+1} \rangle + \langle \alpha_k A^{k+1} p_0, e_k \rangle
+ \langle Ae_{k+1},\alpha_k A^k p_0 \rangle > \langle Ae_{k+1}, e_{k+1}
\rangle$$
which in turn is equivalent to claim that:
$$\langle \alpha_k A^{k+1} p_0, e_k \rangle
+ \langle Ae_{k+1},\alpha_k A^k p_0 \rangle > 0$$
From this expression we can collect term $\alpha_k$ thanks to linearity of the
dot-product:
$$\alpha_k (\langle A^{k+1} p_0, e_k \rangle
+ \langle Ae_{k+1}, A^k p_0 \rangle) > 0$$
and we can further "ignore" the $\alpha_k$ term since we know that all
$\alpha_i$s are positive by definition:
$$\langle A^{k+1} p_0, e_k \rangle
+ \langle Ae_{k+1}, A^k p_0 \rangle > 0$$
Then, we convert the dot-products in their equivalent vector to vector product
form, and we plug in the definitions of $e_k$ and $e_{k+1}$:
$$p_0^T (A^{k+1})^T (\sum_{i=k}^{N} \alpha_i A^i p_0) +
p_0^T (A^{k})^T (\sum_{i=k+1}^{N} \alpha_i A^i p_0) > 0$$
We then pull out the sum to cover all terms thanks to associativity of vector
products:
$$\sum_{i=k}^N (p_0^T (A^{k+1})^T A^i p_0) \alpha_i+ \sum_{i=k+1}^N
(p_0^T (A^{k})^T A^i p_0) \alpha_i > 0$$
We then, as before, can "ignore" all $\alpha_i$ terms since we know by
definition that
they are all strictly positive. We then recalled that we assumed that A is
symmetric, so $A^T = A$. In the end we have to show that these two
inequalities are true:
$$p_0^T A^{k+1+i} p_0 > 0 \; \forall i \in [k,N]$$
$$p_0^T A^{k+i} p_0 > 0 \; \forall i \in [k+1,N]$$
To show these inequalities are indeed true, we recall that A is symmetric and
positive definite. We then consider that if a matrix A is SPD, then $A^i$ for
any positive $i$ is also SPD[^1]. Therefore, both inequalities are trivially
true due to the definition of positive definite matrices.
[^1]: source: [Wikipedia - Definite Matrix $\to$ Properties $\to$
Multiplication](
https://en.wikipedia.org/wiki/Definite_matrix#Multiplication)
Thanks to this we have indeed proven that the delta $\|e_k\|_A - \|e_{k+1}\|_A$
is indeed positive and thus as $i$ increases the energy norm of the error
monotonically decreases.